Serpentine Locomotion Articulated Chain: ANA II - A. M. Cardona; J. I. Barrero; C. Otálora; C. Parra (Applied Bionics and Biomechanics)
When humanity faces challenges in solving problems beyond their technical resources, and has no foundation to solve a problem, engineering must search for an answer developing new concepts and innovative frameworks to excel these limitations and travel beyond our capabilities. This project “Serpentine locomotion articulated chain: ANA II” is a self-contained robot built to evaluate the behavior of the platform being capable of serpentine movements, in a modular chain mechanical design, based on a master/slave architecture.